Induction of Epidermal Rearchitecting of Cocoyam Accessions Caused by Environmental Stressors - Ajah, Florence O.; Osuji, Julian O.; Anoliefo, Geoffrey O. (Current Perspectives in Agriculture and Food Science Vol. 3, 2023)
The effects of two oilfield chemicals on the epidermal morphology of cocoyam accessions were studied. Eight accessions of cocoyam species were exposed to different concentrations of sodium azide and potassium chromate (2.5, 5, 7.5 and 10 mg/kg) while the accessions without any chemical additive were used as the controls. Results showed that cocoyam species were amphistomatous, and had more stomata on the abaxial epidermes. Brachyparacytic stomata were the basic type of stomata observed while other types of stomata (brachyparacytic, amphibrachyparacytic, brachyparatetracytic and brachyparahexacytic-monopolar) were also present in some accessions. Sodium azide treatments induced higher stomatal indices and frequencies in the accessions than potassium chromate treatments; statistical evidence showed a 5 % significant difference between the stomatal indices of the treated accessions. The study confirmed that cocoyam species are poor environmental bioindicator.